Transcriptome dynamics of the suprachiasmatic nucleus and associations with psychiatric disease - Pembroke, W (2016)
The mammalian suprachiasmatic nucleus (SCN) drives daily rhythmic behaviour and physiology, yet a comprehensive understanding of its coordinated transcriptional programmes is lacking. Furthermore, there has been a long-standing association between circadian disruption and psychiatric disease, whose mechanism underpinnings are unknown. To analyse in detail the circadian transcriptome of the mammalian SCN and its variation in psychiatric disease, whole transcriptome sequencing (RNA-seq) of the mouse SCN was performed over a 24-hour light / dark cycle in both wild-type and blind-drunk (Bdr), a mutant strain for Snap25 that shows both schizophrenic endophenotypes and abnormal circadian behaviours. 2,648 novel intergenic long non-coding RNAs were identified using the SCN RNA-seq data, together with novel exons of annotated protein-coding genes, including the clock gene Cry1. Furthermore, in addition to identifying 4,569 genes which exhibited a classic sinusoidal expression signature, co-expression network analysis identified a group of 766 genes which unexpectedly peaked twice, near to both the start and end of the dark phase; this twin-peaking group is significantly enriched for synaptic transmission genes that are crucial for light-induced phase-shifting of the circadian clock. This twin-peaking module is also dysregulated in Bdr, which may provide clues to the molecular pathways linking circadian disruption with psychiatric disease. These findings offer novel insight into SCN biology and suggest that transcriptional timing in the SCN contributes to gating clock resetting mechanisms which, when disrupted, may play a role in psychiatric disease.